Racial/ethnic and sex differences in the ability of metabolic syndrome criteria to predict elevations in fasting insulin in adolescents - DeBoer, Mark D. (2011)
OBJECTIVE: To evaluate racial/ethnic and sex differences in the relationship between metabolic syndrome (MetS) diagnosis and fasting insulin among adolescents. STUDY DESIGN: We analyzed data from the National Health and Nutrition Evaluation Survey 1999–2008 for 3,693 non-Hispanic-white, non-Hispanic-black and Hispanic adolescents (12–19y). We used linear regression to evaluate differences in fasting insulin between those with and without an adolescent adaptation of ATPIII-MetS in a sex- and race/ethnicity-specific basis. RESULTS: Females had higher insulin levels than males and non-Hispanic blacks and Hispanics had higher levels than non-Hispanic whites. Adolescents with MetS had higher insulin levels than those without MetS. The difference in insulin levels between those with and without MetS was greater among non-Hispanic blacks compared with non-Hispanic whites (p<0.05) but not Hispanics (p=0.10). The sensitivity of MetS for detecting elevated insulin levels was lower among non-Hispanic blacks and females compared with other ethnicities and males, respectively. Correlations between insulin and individual MetS components were similar among ethnicities. CONCLUSION: MetS diagnosis performed more poorly in predicting elevated insulin levels among non-Hispanic blacks and among females. These data support the hypothesis that non-Hispanic blacks do not meet current criteria for MetS until they have reached a more advanced degree of insulin resistance.